Implementation of Default Settlement in Event Organizer Service Agreements During the Covid-19 Pandemic with Clients (Case Study of The West Jakarta District Court Decision Number 25/Pdt.G.S/2020/PN.Jkt.Brt) - Daru Pratama (CV. Rayyan Dwi Bharata, 2022)
President Joko Widodo announced that an Indonesian citizen had been confirmed positive for COVID-19 on March 2, 2020. Starting from the spread of covid-19 in Indonesia, the President of Indonesia issued Presidential Decree of the Republic of Indonesia Number 12 of 2020 concerning the Determination of the Nonalam Disaster of the Spread of Corona Virus Diesease 2019 (Covid-19) which stipulates the spread of covid-19 to be a non-natural disaster. This normative legal research discusses the settlement of defaults on the basis of force majeure due to the COVID-19 pandemic. This research uses secondary data types using primary legal materials and secondary legal materials and is carried out with a statute approach, and a case approach. Based on Article 1233 of the Civil Code (KUHPerdata) which reads